Sensitive Intervention Policy Recommendations to Reduce Stunting Rates Based on Spatial Analysis of Sanitary Factors in DKI Jakarta Province 2021 - Irawati, Septiria; Hermawati, Ema (UI Scholars Hub, 2023)
The purpose of this study was to describe the prevalence of stunting in children under five and the percentage of proper sanitation, as well as recommendations for priority areas for stunting control interventions in the Province of the Special Capital Region of Jakarta in 2021. This study used a descriptive approach to present an overview of the percentage of sanitation and prevalence of stunting in children under five by sub-district in 38 districts in DKI Jakarta. Data is displayed as a map to show distribution areas based on high, medium, and low categories. An overlay was made between the distribution map of the percentage of sanitation and the prevalence of stunting to determine the areas with the highest risk. Analysis was carried out on the area's characteristics obtained from the spatial mapping results to determine the recommended intervention program policies. Based on the results of the overlay on the distribution of stunting prevalence and sanitation percentage maps, the recommended areas for priority intervention are Tambora, Sawah Besar, Johar Baru, Senen, Menteng, Jatinegara, Tebet, and Mampang Prapatan sub-districts. The recommended program to be carried out is sensitive interventions consisting of improving sanitation facilities and increasing knowledge and perceptions about sanitation. Improving sanitation facilities means increasing access to gooseneck latrines with septic tanks and access to clean water. Increasing knowledge and perception of the importance of sanitation to prevent stunting is carried out intensively and routinely through community activities and optimizing the role of community leaders.